Ethnography of Communication of Arthur Dimsdalle in Scarlet Letter Movie by Roland Joffe - Chotimah, Chusnul (2010)
This research is aimed at finding the ethnography of communication of Arthur Dimsdalle in Scarlet Letter Movie by Roland Joffe. It was found by analyzed Arthur's communication use components communication's Dell Hymes or called SPEAKING grid. The type of this research is descriptive qualitative research. In collecting the data, the writer uses documentation method by selecting Arthur's excerpt based on the movie script of Scarlet Letter movie. To achieve the objective, the writer takes Arthur's dialogue that relates with components of communication in analyzes. It dialogue describes form of components of communication. The research finds that components of communication of Arthur Dimsdalle are (1) Scenes/settings, (2) participants, (3) ends, (5) keys, (6) instrumentalities, (7) norms, (8) genres. Based on the finding of components of communication of Arthur find ethnography of communication of Arthur Dimsdalle is obedient to the religion as the influence of Arthur in communication. Another that respect to Arthur by the society also became the influence to Arthur's communication. This research shows that culture is part of way of human communication. The norm in the culture that obedient and respected is influenced to the way of life especially communication. It makes the study of discourse enlarge with this finding. It is proved that culture and linguistic is has connection. Both are influence each other in the society